Vulvar diseases - Turner, Maria L.; Marion & Roberta Sulzberger Institute for Dermatologic Communication and Education; American Academy of Dermatology. Committee on Audiovisual Education ([Evanston, Ill.] : American Academy of Dermatology, Committee on Audiovisual Education, 1988)
(Producer) Clinical features of diseases of the vulva, including inflammatory diseases, infections, and tumors. Normal anatomical structures are also presented in clinical photographs and diagrams
'From the collections of Maria L. Turner.'
Keywords: Vulvar Diseases